PRELIMINARY STUDY OF MOLLUSCAN DIVERSITY IN PARIYAT RIVER, JABALPUR (M.P.) - Bhandari, Rita; Shukla, Arjun; Rai, Shivani (International Journal of Research -GRANTHAALAYAH, 2016)
Mollusca diversity of Pariyat River was studied during June 2015 to April 2016. After construction of Dairies in the surroundings and bank of Pariyat River, a major part of running water is being converted in to sludge. Mollusca fauna is correlated with biological and various physico-chemical parameters that regulate abundance and distribution of different species. In present study, attempts have been made to collect, classify and identify Mollusca of Pariyat River in Panagar region. The survey indicated that 157 individuals from 13 families of Mollusca were found in this zone of the river. Out of 13 families of Mollusca 9 species are belonging to class Gastropoda and 3 species to class Bivalvia. The major Mollusca abundance was noticed viz. Pila sp. and Bellamya sp. Shannon’s Diversity Index (H) was calculated from the recorded 157 individuals has value -1.024955387 which is inverse to Simpson’s Index (C) has value 0.10462899. Diversity indices indicate a good ratio of species diversity in the study site. In future, habitat destruction, introduction of sludge and pollution lead to decline of species. An urgent need exists for studying the life history traits and demography of the most important threatened Mollusca, as lack of information on these aspects have significantly affected conservation efforts.